Bending‐Insensitive Intrinsically Flexible Ultraviolet Encoding Devices Based on Piezoelectric Nanogenerator‐Supplied Liquid Crystalline Polymer Fabrics. Issue 33 (24th July 2022) - Zheng, Xiaoxiong; Liu, Zhefeng; Wang, Rui; Chen, Aihua
Abstract: It is significantly challenging for state‐of‐the‐art wearable electronics to stably monitor physicochemical signals under dynamic motions. Herein, a bending‐insensitive, self‐powered, and intrinsically flexible UV detector has been realized based on well‐designed oriented composite fabrics, consisting of ionic liquid (IL)‐containing liquid crystalline polymers (ILCPs) and piezoelectric poly(vinylidene fluoride‐trifluoroethylene) [P(VDF‐TrFE)] nanogenerators. The novel composite fabrics establish effective UV illuminance‐internal stress‐electric signal conversion by coupling resistive and piezoelectric effects, with a fast response time of 190 ms. Particularly, benefiting from the intrinsic flexibility of composite fabrics, the ILCP/P(VDF‐TrFE) device can maintain stable performance under dynamic bending even if the frequency is up to 2.5 Hz, with a bending insensitivity of less than 1% performance variation under 1.0 mW cm −2 UV light. Combined with the Internet of Things and the American Standard Code for Information Interchange (ASCII), wearable encoding electronics have been successfully implemented with a printing speed of 3.2 s per character under dynamic bending. Abstract : Well‐designed piezoelectric nanogenerator‐supplied ionic liquid (IL)‐containing liquid crystalline polymer (ILCP) composite fabrics are demonstrated to prepare bending‐insensitive and self‐powered wearable UV detectors, with fast response time of 190 ms. The device can guarantee stable UV communication even under dynamic bending frequency of 2.5 Hz, extending practical applications under various extreme and special environments.